Novel bacterial cluster “Prevotella, Bacteroides and Suterella” associated with mortality in Mexican patients with acute-on-chronic liver failure (ACLF) and clinical utility of systemic hs-CRP and IL-6: A frontier approach involving next-generation sequencing at the intestinal level in a cohort by alcoholic etiology. - Paula A. Castaño Jiménez; Tonatiuh A. Baltazar-Díaz; Rodrigo Hernández-Basulto; Mayra P. Padilla-Sánchez; Ksenia K. Kravtchenko; Roxana García-Salcido; María T. Tapia-De la paz; Kevin J. Arellano-Arteaga; Luz A. González-Hernández; Miriam R. Bueno-Topete (Annals of Hepatology)
Introduction and Objectives: ACLF is characterized by acute decompensation of cirrhosis, organ failure, and high short-term mortality. Several studies have demonstrated the relevance of intestinal microbiota (IM) in the pathophysiology of cirrhosis. To date, there are no studies in the Mexican population focused on IM in alcohol-associated ACLF and its relationship with mortality and inflammatory markers. Aim: To analyze the composition and diversity of IM in patients with alcohol-associated cirrhosis and ACLF, healthy controls, and its correlation with inflammatory markers. Materials and Patients: Cross-sectional study, which included 22 decompensated patients with ACLF, 16 decompensated patients without ACLF (CD) and 18 healthy individuals (HI), recruited at the Hospitales Civiles de Guadalajara. Fecal IM was characterized by NGS of the 16S-rRNA gene. Systemic levels of high-sensitivity C-reactive protein (hs-CRP) and interleukin 6 (IL-6) were quantified by ELISA, and bioinformatics analysis of IM was performed using the QIIME2 package. Quality filtering, which includes removal of chimeras and non-biological sequences, was performed using the DADA2 algorithm. Resulting ASVs were taxonomically assigned through a self-trained naïve Bayesian classifier, against the SILVA database. Furthermore, α and β diversity analyses, relative abundances, and ANCOM-BC compositional analysis were performed in the QIIME2 package. Predictive values and associations were performed using ROC curves and Spearman correlations, respectively. Results: ACLF and CD patients showed significantly lower α-diversity compared to CS. The comprehensive bacterial taxonomy profile in ACLF was significantly dominated by pathogenic/inflammatory genera such as Escherichia/Shigella, Enterobacter and Prevotella. In contrast, we observed a depletion of Bacteroides compared to CD. Interestingly, the subanalysis of MI in ACLF patients categorized at 7 and 90 days of mortality showed consistency with the enrichment of the Prevotella, Bacteroides and Suterella cluster. The Proteobacteria/Firmicutes ratio as a potential marker of dysbiosis, was significantly elevated in ACLF patients. Serum levels of hs-CRP and IL-6 were potentially increased in ACLF, in comparison to CD and CS. hs-CRP correlated positively with IL-6 and the Proteobacteria/Firmicutes ratio and negatively with α-diversity. IL-6 levels were positively correlated with MELD-Na. Finally, ROC curve analyses showed that hs-CRP allows discrimination of infections in patients with CD with a cut-off point >70.7 mg/L (AUROC: 0.75, with 90% sensitivity and 68.9% specificity). IL-6 allows discrimination of hepatic encephalopathy (HE) in patients with CD and ACLF with a cut-off point >7051.1 pg/mL (AUROC: 0.67, with 81.4% sensitivity and 45.8% specificity). Conclusions: The dysbiotic/proinflammatory profile of IM in ACLF correlated with the potential increase in systemic inflammation. The bacterial cluster “Prevotella, Bacteroides and Suterella” represents a hallmark of mortality within 7 and 90 days. IL-6 and hs-CRP allow discrimination of HE and infections in patients with alcohol-associated cirrhosis.